Study of Corrosion Inhibition Mechanism of Sputter-Deposited W-42Cr-5Ni and Cr-10Zr-10w Alloys by Sodium Nitrite as Green Inhibitor in 0.5 M NaCl and 1 M NaOH Solutions - Subedi, Dhruba Babu; Pokharel, Durga Bhakta; Bhattarai, Jagadeesh (International Journal of Applied Sciences and Biotechnology, 2014)
The effect of different concentrations of sodium nitrite as a green corrosion inhibitor on the corrosion inhibition mechanism of the sputterdeposited ternary W-42Cr-5Ni and Cr-10Zr-10W alloys was studied in 0.5 M NaCl and 1 M NaOH solutions open to air at 25ºC using corrosion tests. The use of the sodium nitrite enhanced the corrosion resistance properties of both the alloys in 0.5 M NaCl and 1 M NaOH solutions. It is found that the sodium nitrite is strongly adsorbed on the surface of the sputter-deposited these two alloys by physical adsorption, not by the chemisorption. As a result the corrosion resistance property of the alloys was found to be significantly increased with increasing the concentration of the green corrosion inhibitor of sodium nitrite. The corrosion rates of the sputter-deposited W-42Cr-5Ni and Cr-10Zr-10W alloys were decreased with increasing the concentrations of sodium nitrite of 2400 ppm. DOI: http://dx.doi.org/10.3126/ijasbt.v2i4.11531Int J Appl Sci Biotechnol, Vol. 2(4): 537-543